Modern approach to diagnostics and management of pregnant women with placenta previa (Eurasian Medical Research Periodical, 2025)
Placenta previa occurs in 1.5% of all pregnancies and predisposing factors for the development of placentation anomalies are the so-called "diseases of the operated uterus" - dystrophic changes in the endometrium due to the presence of multiple damages to the integrity of the layers of the uterine wall against the background of previous cesarean sections, conservative myomectomies, abortions. It has been established that the course of pregnancy with placenta previa is accompanied by a large number of complications, such as miscarriage, placental disorders, fetal growth retardation syndrome (Shmakov R.G. et al., 2018; Yashchuk A.G. et al., 2020; Bushtyrev A.V. et al., 2016). Despite the fact that in the structure of obstetric bleeding, bleeding associated with uterine hypotension is the most common, bleeding associated with placenta previa ranks among the causes of massive obstetric bleeding